2013
DOI: 10.1155/2013/205963
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Weight, Body Mass Index, and Bone Mineral Density in Men Referred for Dual-Energy X-Ray Absorptiometry Scan in Isfahan, Iran

Abstract: Objective. Although several studies have investigated the association between body mass index (BMI) and bone mineral density (BMD), the results are inconsistent. The aim of this study was to further investigate the relation between BMI, weight and BMD in an Iranian men population. Methods. A total of 230 men 50-79 years old were examined. All men underwent a standard BMD scans of hip (total hip, femoral neck, trochanter, and femoral shaft) and lumbar vertebrae (L2-L4) using a Dual-Energy X-ray Absorptiometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 34 publications
9
51
1
3
Order By: Relevance
“…Significant positive correlation of BMI and BMD has been reported in literature but our study failed to confirm this [11][12][13][14][15]. The reason might be because of non-significant difference between the weight of controls and cases.…”
Section: Resultscontrasting
confidence: 83%
“…Significant positive correlation of BMI and BMD has been reported in literature but our study failed to confirm this [11][12][13][14][15]. The reason might be because of non-significant difference between the weight of controls and cases.…”
Section: Resultscontrasting
confidence: 83%
“…In addition to DEXA, osteoporosis examination can be done with BMI [16]. Overweight and obesity have been considered protective to bone health, while higher BMI levels to be associated with higher BMD score [17][18][19][20]. In this study, the height and weight were positively correlated with BMD and the same result.…”
Section: Discussionsupporting
confidence: 50%
“…For simple regressions using body weight and BMI as independent variables, the correlation coefficients were positive, indicating that an increase in weight, and BMI, leads to an increase in spinal BMD. This finding is consistent with other studies that have shown a positive association between body weight and BMD in women after menopause [22], between BMI and BMD, and between weight and BMD in men [16], and between BMI and BMD regardless of age, sex, or race [23].…”
Section: Discussionsupporting
confidence: 93%
“…Anthropometric and reproductive variables represent risk factors of greater importance for osteoporosis than the risk factors related to life style [14]. A low body mass index (BMI) is a risk factor for bone loss [15], and being overweight has a protective effect against osteoporosis [16]. The outcomes of another study showed that women with postmenopausal osteoporosis do not have a higher BMI than the values recommended by the National Institutes of Health [17].…”
Section: Resultsmentioning
confidence: 99%